Teaching Tourism Terminology to Students - Gafurova Norjon Nematovna (Genius Journals, 2023)
In this scientific article it is described that the problem of teaching students to Tourism terms. In the process of teaching terms about tourism specialty it requests taking into consideration the linguistic peculiarities of those terms. Thus, the purpose of studying the terms related to tourism in English is to increase the vocabulary of students in the profession and to form their skills in working with texts related to tourism in English. It is necessary to take into account the achievements of modern linguistics, to generalize the modern perception of terms by students in English and to provide continuous training to future professionals, as well as the need to create a new generation of textbooks on terminology.
Keywords: modern linguistics; terms; teaching process; specific terminology